Upon an attack in Nahum 2:2 - Pinker, Aron (The journal of Hebrew scriptures, 2003)
Two options for emending the first prosaic colon of Nah 2:2 into two poetic cola are suggested. If accepted they give all the cola the same poetic structure and perhaps bring out some military nuances of the attack on Nineveh.